Production of virus-free quality planting material in banana (Musa spp.) variety CO 3 (ABB) through meristem culture - Thanuja, K; Arulmozhiyan, R; Saraswathi, M S; Selvarajan, R; Jegadeeswari, V; Babu, V R (Plant Science Today, 2025)
The rapid spread of pest and disease infestations significantly affects agricultural productivity and food security. Diseases caused by fungi, bacteria, viruses and other pathogens can severely impact plant health, leading to substantial crop losses. Some crop species, like banana (Musa spp.), transmit viral diseases mostly through vegetative propagules but very rarely through seeds. To address this issue, meristem culture was employed in the present study on the banana variety CO 3 (ABB) to produce virus-free plantlets. Meristem tips, ranging from 20-30 mm in size, were established on fullstrength MS medium supplemented with vitamins, ascorbic acid, myoinositol, 2 mg/L BAP and 0.5 mg/L IAA during the initiation phase. MS medium with 3 mg/L BAP and 0.5 mg/L IAA was optimal for multiple shoot formation, producing an average of 8.5 shoots per explant in 52.5 days. Regarding growth parameters, approximately 3.7 leaves per explant were observed, with an average leaf length of 4.56 cm and an average leaf width of 1.89 cm after the fifth subculture and before the rooting stage. The meristem tips (20-30 mm) of the CO 3 (ABB) variety produced approximately 92.5% virus-free plantlets with a survival rate of 86.5%. The derived plantlets were successfully hardened.